Central banking in Malaysia : a study of the development of the financial system and monetary management - Lock, Lee Hock. (Singapore : Butterworths, 1987)
In the light of financial liberalisation and reforms since the 1980s, the financial system in the country has undergone significant structural developments. Similarly, the economy also experienced two recessions. A mere update of the fourth edition of the Money and Banking in Malaysia (1954-1994) for the 40th anniversary would not do justice in planning this new book "The Central Bank and the Financial System in Malaysia - A Decade of Change (1989-1999)" in conjunction with the 40th anniversary of the Bank. This book presents a description and analysis of the significant structural changes in the financial system and the economy during the past decade, a period which was marked by significant changes and challenges, and aptly termed a decade of change.
Includes Bibliographical references and Index.
aia 07/05/2018
Loans
Keywords: Banks and Banking, Central; Monetary policy $1 (BMalaysia.s; Malaysia